Rock dust and humic substance promote chloroleucon dumosum seedling growth - Pereira, Maria Janiele Barbosa de Farias; Leite, Jakson; Lima, Roberta; Vieira Silva, José; Botero, Wander; Moura, Flavia (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The effects of humic substances as well as silicate rocks as a source of nutrients in agriculture is a common strategy, but the specific effects of these substances on native trees are still poorly known. The application of these inputs in the production of seedlings for restoration depends on the analysis of their effects on the various parts of the plants, mainly on the root system, which plays an important role in the survival of the seedlings after planting. In this study, we used morphological, anatomical, and nutrient uptake data to report the effects of rock dust and humic substance in the growth of the slow-growing Chloroleucon dumosum. The experiment consisted of four treatments in scenarios with presence and absence of rock dust and peat humic substances in the best concentration obtained in a previous experiment. The treatments were repeated nine times in a randomized block design (DBC) arrangement. Seeds were sown in pots (1.7 L) with soil and sand substrate (2:1). SH promoted root growth of C. dumosum and the response was dependent on the source and its concentration. The rock powder promoted the dry mass of C. dumosum shoot at 60 days after the treatments. In treatments containing rock dust added to the substrate there was a reduction in nodulation. The growth variables were all significant in the treatments with addition of rock dust, with the presence of the highest averages appearing at 90 days after the treatment’s application. Rock dust promoted the growth of C. dumosum and when associated with SHs this growth was more pronounced. There was no significant effect for N, K and Si. The treatments with rock dust presented the lowest phosphorus content in the shoot tissue.